IMPLEMENTATION OF ELECTRONIC STUDENT WORKSHEET BASED ON GUIDED INQUIRY LEARNING MODEL ON CHEMICAL EQUILIBRIUM MATERIAL TO IMPROVE THE STUDENTS’ CREATIVE THINKING SKILLS - Hafidhon Muhlisun Furqon; Dian Novita (Universitas Negeri Surabaya, 2021)
The research purpose is to determine the Electronic Student Worksheet (E-SW) validation results, the implementation of learning, the activities of students, the learning outcomes of creative thinking skills, the realm of knowledge, and students' responses. Furthermore, research focuses on guided inquiry learning models to improve students' creative thinking skills. The research population was senior high school students. The sample in the research was 36 high school students. This research model uses One-Group Pretest-Postest Design to collectto collect the data using observation and test methods. The data analysis technique consisted of two stages: the n-gain value test and the independent sample t-test manually. The first stage of the test for the N-gain value test in students obtained medium and high criteria. The second stage of the independent sample t-test showed significant changes between before and after learning. The results showed that the guided inquiry learning model on chemical equilibrium material could improve the creative thinking skills of high school students.